Displacement of hydrogen position in di-hydride of V-Ti-Cr solid solution alloys. (1st August 2022) - Sakaki, Kouji; Kim, Hyunjeong; Majzoub, Eric H.; Machida, Akihiko; Watanuki, Tetsu; Ikeda, Kazutaka; Otomo, Toshiya; Mizuno, Masataka; Matsumura, Daiju; Nakamura, Yumiko
Abstract: Local structure in the di-hydride (di-deuteride) phases of V-Ti-Cr solid solution alloys (V10 Ti35 Cr55, V50 Ti20 Cr30 and V80 Ti8 Cr12 ) were investigated using synchrotron X-ray and neutron total scattering experiments. Both Rietveld refinement and pair distribution function (PDF) refinement of the X-ray scattering data indicated that the crystal structure of the metal lattice was a face centered cubic (FCC) structure and no difference between their local structure and average structure was observed. Rietveld refinement of neutron scattering data showed that the crystal structure was a CaF2 structure. However, the CaF2 structure model did not reproduce the first peak corresponding to the metal-hydrogen correlation in neutron PDF patterns. When special quasi-random structure (SQS) models based on the CaF2 structure are applied for the refinements, the SQS structure model, relaxed via first-principles calculations, reproduced the whole neutron PDF pattern. Distribution of interatomic distances between hydrogen and metal atoms in the relaxed SQS models showed that interatomic distance of hydrogen with Cr was shorter than that with V and that with Ti was longer than that with V, independently of the chemical compositions. The combination of neutron PDF and first-principles calculations with the SQS models revealed that hydrogen atoms did not occupy the center of tetrahedron but moved toward Cr atoms and away from Ti. Graphical abstract: Image, graphical abstract